PREDIKSI LAJU EROSI PADA DAERAH TANGKAPAN AIR BENDUNGAN DENGAN METODE USLE (STUDI KASUS : BENDUNGAN TITAB) - Risan Kurnia Ramdhani; Ignatius Sriyana (Politeknik Negeri Semarang, 2022)
Erosion is a serious problem in watershed management. The Saba watershed is a water catchment area at the Titab Dam in Buleleng Regency, Bali Province. The existence of the Titab Dam is accompanied by the development of activities of the surrounding community, both tourism, economic and daily activities. Unfortunately, this activity in the future will have a negative impact on the condition of the dam so that it poses a risk. This study aims to determine the amount of sediment inflow with land erosion approach at the Titab Dam using the USLE (Universal Soil Loss Equation) method. Erosion rate prediction was carried out using the USLE method and with the help of ArcGIS 10.8 software. From the results of the analysis, it was found that in the Titab Dam catchment area, only 3 classes were obtained. The results of the calculation of the erosion rate using the USLE method showed that the magnitude of the erosion was 439,962 tons/year or 53.05 tons/ha/year. In addition, the most influential factors on the rate of erosion are the length and slope factors. In addition, land cover is also one of the most influential factors.